2015
DOI: 10.1080/14786419.2015.1013472
|View full text |Cite
|
Sign up to set email alerts
|

HPLC simultaneous determination of arbutin, chlorogenic acid and 6′-O-caffeoylarbutin in different parts ofVaccinium dunalianumWight

Abstract: Arbutin (1), chlorogenic acid (2) and 6'-O-caffeoylarbutin (3) are three major components in Vaccinium dunalianum Wight with various promising bioactivities. A reliable, reproducible and accurate method for simultaneous and quantitative determination of 1-3 is developed by RP-HPLC analysis. This method should be appropriate for the quality assurance of unprocessed and processed materials of V. dunalianum. The contents of 1-3 in different parts of V. dunalianum from different origins were analysed. The content … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…6′-O-caffeoylarbutin is abundantly found in Vaccinium dunalianumas. V. dunalianumas is a commonly cultivated blueberry species in China and its dried leaf buds as herbal tea while its leaves are used as folk medicine ( Li et al., 2016 ; Luo et al., 2015 ). Sunflower ( Helianthus annuus ) sprouts (nutritious sunflower lettuce) found to be enriched with cynarin ( Sun et al., 2012 ), recommending these foods as beneficial food choice for COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…6′-O-caffeoylarbutin is abundantly found in Vaccinium dunalianumas. V. dunalianumas is a commonly cultivated blueberry species in China and its dried leaf buds as herbal tea while its leaves are used as folk medicine ( Li et al., 2016 ; Luo et al., 2015 ). Sunflower ( Helianthus annuus ) sprouts (nutritious sunflower lettuce) found to be enriched with cynarin ( Sun et al., 2012 ), recommending these foods as beneficial food choice for COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Vaccinium dunalianum Wight is an evergreen, small shrub tree species that is mainly distributed in Sichuan Province, Yunnan Province, Guizhou Province and Tibet. Its leaves have been used as folk medicine for treating articular rheumatism, relaxing tendons, and activating collaterals, and dried leaf buds are used as herbal tea by local people in China (Luo et al 2015). Previous studies found that the leaf buds of V. dunalianum Wight are rich in arbutin, 6 0 -O-caffeoylarbutin and chlorogenic acid (Zhao et al 2008), which exhibit antioxidant, depigmentation (Xu et al 2014) and DNA-protective effects (Jang et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Its leaves have been used as folk medicine for treating articular rheumatism, relaxing tendons, and activating collaterals, and dried leaf buds are used as herbal tea by local people in China (Luo et al . 2015). Previous studies found that the leaf buds of V. dunalianum Wight are rich in arbutin, 6′‐ O ‐caffeoylarbutin and chlorogenic acid (Zhao et al .…”
Section: Introductionmentioning
confidence: 99%
“…In China, V. dunalianum Wight leaves are used as a traditional treatment for articular rheumatism. Additionally, local people use the dried buds of V. dunalianum Wight as a substituted for tea (Luo et al 2015b). Previous studies found that the leaf buds of V.…”
mentioning
confidence: 99%
“…dunalianum Wight is rich in the natural whitening active agent arbutin (Li et al 2017;Luo et al 2015a). However, research on gene expression and molecular biology of V.…”
mentioning
confidence: 99%